THE PROBLEM OF THE RELIABILITY OF EXPRESSING THE TECHNICAL AND TACTICAL CAPABILITIES OF THE Wrestlers IN THE CONDITIONS OF COMPETITION (Scientific journal of the Fergana State University, 2024)
In this article, the factors of the reliability of revealing (demonstrating, using) the technical capabilities of wrestlers at the stages of preparation for responsible competitions are highlighted. Methods of assessing the preparation of wrestlers, showing the technical and tactical possibilities of physical exhaustion (fatigue) of wrestlers, and the effect of their effectiveness on the body are highlighted.